MATHEMATICAL MODELING OF FIBER-OPTIC TRANSMISSION SYSTEM WITH INTENSITY MODULATION - PEDYASH, Volodymyr (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Fibre optic transmission systems are widespread in the transport network. Optical Transport Hierarchy (OTH) transmission systems are the basis of the transport network. The principle of wavelength multiplexing of channels is used to increase the technical and economic performance. Technically a simpler type of intensity modulation is used to transmit OTU1 and OTU2 OTH frames. Erbium-doped fibre-based optical amplifiers also generate amplified spontaneous emission noise, which degrades the performance of the transmission system. The qualitative characteristics of the optical channel of OTH transmission system with intensity modulation are investigated in this paper. In the simulation process, it is possible to neglect the nonlinear signal distortion in the optical fiber at the nominal signal power of the transponder transmitter. Therefore, in the studied transmission system model, an optical oscillation consisting of two components (signal and noise) arrives at the receiver input. In this case, an electrical signal consisting of three summands (signal-signal, signal-noise and noise-noise) will be generated at the output of the photodiode. A simplified formula for calculating the Q-factor of the optical signal, which affects the error probability in the optical channel, is proposed in most of the specialized literature. Numerical Q-factor values were calculated for OTU1 and OTU2 frames. They were compared with the reference results which were obtained by simulation in Optiwave Optisystem software. The analysis of the obtained data has proved that the simplified formula for the calculation of the Q-factor has a relative error of the order of 39-59%. A more accurate result can be obtained by using an expression that takes into account both components of the noise at the photodiode output.